The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/diagnostics8010013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a New Multiplex Immunoassay for Measurement of Ferritin, Soluble Transferrin Receptor, Retinol-Binding Protein, C-Reactive Protein and α1-Acid-glycoprotein Concentrations against a Widely-Used s-ELISA Method

Abstract: Recently, a multiplex ELISA (Quansys Biosciences) was developed that measures ferritin, soluble transferrin receptor (sTfR), retinol-binding protein (RBP), C-reactive protein (CRP), α1-acid glycoprotein (AGP), thyroglobulin, and histidine-rich protein 2. Our primary aim was to conduct a method-comparison study to compare five biomarkers (ferritin, sTfR, RBP, CRP, and AGP) measured with the Quansys assay and a widely-used s-ELISA (VitMin Lab, Willstaett, Germany) with use of serum samples from 180 women and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(25 reference statements)
1
7
1
Order By: Relevance
“…As such, the median relative differences between the Q-Plex and reference assay in our study (Fer -2.4%, sTfR 107%, CRP 0.03%, AGP -1.3%, and RBP 51%) do not correspond well with the 2 previously reported relative differences between the Q-Plex and the commonly-used sandwich ELISA [8,11]: Fer 88% and 108%, sTfR 70% and 148%, CRP -33% and -1%, AGP -53% and -37%, and RBP -16% and 12%. Several reasons could explain these discrepancies: different antibodies with different specificities and affinities used in these comparisons; different sample sets may result in different assay relationships either due to different concentration ranges and/or due to sample composition; the statistical approach used to assess the assay agreement varies across studies and non-constant variance and/or non-constant differences may not have been addressed in previous studies; in previous studies, the authors used the slope to describe the proportional difference between the assays without giving consideration to the intercept, which in some cases was quite large.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…As such, the median relative differences between the Q-Plex and reference assay in our study (Fer -2.4%, sTfR 107%, CRP 0.03%, AGP -1.3%, and RBP 51%) do not correspond well with the 2 previously reported relative differences between the Q-Plex and the commonly-used sandwich ELISA [8,11]: Fer 88% and 108%, sTfR 70% and 148%, CRP -33% and -1%, AGP -53% and -37%, and RBP -16% and 12%. Several reasons could explain these discrepancies: different antibodies with different specificities and affinities used in these comparisons; different sample sets may result in different assay relationships either due to different concentration ranges and/or due to sample composition; the statistical approach used to assess the assay agreement varies across studies and non-constant variance and/or non-constant differences may not have been addressed in previous studies; in previous studies, the authors used the slope to describe the proportional difference between the assays without giving consideration to the intercept, which in some cases was quite large.…”
Section: Discussioncontrasting
confidence: 92%
“…Conversion equations may be helpful in the future to allow comparison of Q-Plex assay data with US population data generated with the reference-type assays in the National Health and Nutrition Examination Survey. Previous studies that compared the Q-Plex and sandwich-ELISA assay with samples from African and Asian countries, appeared to cover similar concentration ranges to our study based on visual inspection of the scatter plots or Bland-Altman plots [8,11]. Still, the equations derived in this study should be confirmed with other sample sets, particularly from countries where analyte concentrations are different from those in the United States.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Yet, for several of their surveys, samples were analyzed at the VitMin lab (Juergen Erhardt; http://www.nutrisurvey.de/blood_samples/ ), which uses a sandwich ELISA method to measure ferritin, retinol-binding protein, soluble transferrin receptor, CRP, and AGP ( 9 ). The VitMin lab has been a valued resource in the global micronutrient research community for many years; an initial validation study of its ELISAs was promising ( 9 ), although recent comparisons of the VitMin method to a new commercial assay showed poor concordance ( 10 ). For the surveys for which samples were analyzed at the VitMin lab, detailed measures of assay technique, measures of precision, and limits of quantification could have been feasibly obtained and assessed as part of the BRINDA project.…”
mentioning
confidence: 99%